Ligand-free electrodeposition method for synthesizing platinum nanowire array on substrate
Synthesizing platinum nanowire arrays on the substrate through ligand-free electrodeposition methods has solved the problem of difficulty in synthesizing high-quality platinum nanowires under template-free and ligand-free conditions in the prior art, and the potential for efficient synthesis of platinum nanowires and application in fuel cells and other fields is achieved.
Patent Information
- Application Number
- CN202510108388.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The prior art is difficult to synthesize high-quality platinum nanowires without templates and ligands, and the morphology and size of the nanowires are easily destroyed during the removal of templates or ligands.
Platinum nanowire arrays were synthesized on the substrate by ligand-free electrodeposition method, and the length and density of nanowires were controlled by regulating the deposition time and APTES concentration. The synthesis of platinum nanowires was achieved in a wide growth potential window using the constant potential ampere method.
The synthesis of platinum nanowire arrays of different lengths under template-free and ligand-free conditions has exceeded the limitations of traditional methods and improved the quality and application potential of nanowires, and is particularly suitable for fuel cells and electrochemical catalysis fields.
Smart Images

Figure CN119859827A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano material synthesis and relates to a ligand-free electrodeposition method for synthesizing a platinum nanowire array on a substrate. Background Art
[0002] One-dimensional platinum-based nanomaterials have shown broad application potential in many fields such as catalysis, energy, electronics, and biomedicine due to their unique structure and properties, including advantages such as high aspect ratio, large specific surface area, and fast electron transport. However, this one-dimensional morphology makes the synthesis of platinum nanowires quite challenging. Because metal crystals usually have highly symmetrical lattices and lack the inherent tendency of one-dimensional anisotropic growth. Therefore, the current methods for synthesizing platinum nanowires are mainly based on the use of templates and ligand-assisted growth. Usually, the synthesis of longer platinum nanowires is achieved within the template, but the assembly and subsequent removal of these templates are complicated and involve strict conditions and reagents; in addition, it is difficult to find a suitable template with a pore channel of the desired diameter and length, and to completely remove the template without affecting the integrity of the nanowire.
[0003] In addition, in the ligand-assisted synthesis of platinum nanowires, the most commonly used ligands are oleylamine and polyvinyl pyrrolidone. However, from a traditional perspective, when nanowires are used as catalysts, the ligand layer on their surface blocks the catalytic active sites; and it is difficult for platinum to grow in one dimension without the assistance of templates or ligands. This may be related to the inherent isotropic crystal growth behavior of platinum. Unlike other precious metals such as Au and Ag, the surface energy difference between different faces of Pt is usually greater than the surface energy difference between the corresponding Au and Ag surfaces, so it is difficult to achieve morphological transformation by fine-tuning the reaction parameters.
[0004] Therefore, considering the side effects of ligands on nanocatalysis, people have also developed a variety of strategies to remove ligands, but the morphology and size of nanowires will inevitably be destroyed in the process of removing ligands. Therefore, it is still a huge challenge to synthesize high-quality platinum nanowires under ligand-free conditions. Summary of the invention
[0005] The purpose of the present invention is to provide a ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate. The present invention utilizes an electrochemical deposition method, which has a wide growth potential window (-0.5 V to -7 V). Platinum nanowire arrays of different lengths can be obtained by regulating the deposition time, and the density of the platinum nanowire arrays can be controlled by changing the APTES concentration. In addition, the synthesis can also be extended to a conductive substrate, so that the platinum nanowire array can be directly used as a working electrode in the future, providing great application potential for fields such as electrocatalysis. The present invention has a simple process, mild reaction conditions, low cost, and the electro-deposition method for synthesizing nanomaterials has the advantages of precise controllability, simple operation and environmental protection.
[0006] In order to solve the technical problem of the present invention, a technical solution is proposed: a ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate, comprising the following steps:
[0007] (1) First, the substrate is treated to be hydrophilic by a plasma cleaner, and then the substrate is treated to be amino by using a triaminopropyltriethoxysilane solution (APTES) under acidic conditions;
[0008] (2) taking out the substrate in step (1), rinsing off excess APTES solution, and immersing the substrate in a platinum particle solution;
[0009] (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte;
[0010] (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode; the electrolyte is composed of water and ethanol, in which chloroplatinic acid is used as the metal precursor, and no additional ligand is added;
[0011] (5) The electrodeposition synthesis method uses the constant potential amperometry method, with the potential set at -0.5 V to -10 V and the deposition time controlled at 5 min-180 min. After the electrodeposition reaction is completed, the silicon wafer is removed, rinsed with water and ethanol, and dried before characterization.
[0012] Preferably, the method comprises the following steps:
[0013] (1) First, the substrate is treated to be hydrophilic by a plasma cleaner, and then the substrate is treated to be amino by using a triaminopropyltriethoxysilane solution (APTES) under acidic conditions;
[0014] (2) Take out the substrate in step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution;
[0015] (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte;
[0016] (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode; the electrolyte is composed of water and ethanol, in which chloroplatinic acid is used as the metal precursor, and no additional ligand is added; the pH value of the electrolyte is 1.25~2.79;
[0017] (5) The electrodeposition synthesis method uses the constant potential amperometry method, with the potential set at -0.5 V to -7 V and the deposition time controlled at 5 min-180 min. After the electrodeposition reaction is completed, the silicon wafer is removed, rinsed with water and ethanol, and dried before characterization.
[0018] Preferably, in step (1), the concentration of triaminopropyltriethoxysilane is 5 mM.
[0019] Preferably, the substrate is a silicon wafer, hydrophobic carbon paper, hydrophilic carbon paper, hydrophobic carbon cloth or conductive glass.
[0020] Preferably, in step (1), the silane coupling agent used for functionalizing the substrate may be triaminopropyltriethoxysilane (APTES) or tricyanopropyltriethoxysilane (CPTES).
[0021] Preferably, in step (1), the acid used to treat the substrate is acetic acid.
[0022] Preferably, in step (4), in step (4), the total volume of the electrolyte is 12 mL, the volume ratio of water to ethanol is 2:1, the concentration of chloroplatinic acid is 1.2-2.4 mM as a metal precursor, dissolved in water, and no additional ligand is added during the synthesis.
[0023] Preferably, the method comprises the following steps:
[0024] (1) First, the substrate was treated with hydrophilicity by a plasma cleaner for 10 min, and then the substrate was treated with amino by using triaminopropyltriethoxysilane solution APTES for 30 min under acidic conditions. The concentration of triaminopropyltriethoxysilane was 5 mM. APTES was dissolved in equal volumes of ethanol and water in a ratio of 1:1. During the preparation, ethanol was added first and then water to prevent excessive hydrolysis of the silane coupling agent. After the APTES was prepared, it was mixed with an equal volume of 17.4 M acetic acid to treat the substrate.
[0025] (2) Take out the substrate from step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution for 2 h;
[0026] (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte;
[0027] (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode. The total volume of the electrolyte is 12 mL, which is mainly composed of water and ethanol, and the volume ratio of water to ethanol is 2:1. Among them, 1.2 mM chloroplatinic acid is used as a metal precursor and dissolved in water. No additional ligand is added during the synthesis, but a certain amount of 2 M hydrochloric acid is added. The pH value of the electrolyte is measured to be 1.82;
[0028] (5) The constant potential amperometry method was used in the synthesis, and the deposition time was 120 min. After the deposition, it was washed with ethanol and water and dried before characterization. The surface of the substrate was covered with a layer of black film, indicating that the platinum nanowire array was successfully synthesized.
[0029] In order to solve the technical problem of the present invention, another technical solution is proposed: the platinum nanowire array can be used in the field of fuel cells or electrochemical catalysis.
[0030] Beneficial effects:
[0031] Compared with the existing technology, the present invention can synthesize platinum nanowire arrays of different lengths, and the longest can reach about 10 μm, which is a length that cannot be achieved on a flat substrate at present. This technology breaks through the limitations of templates and ligands, and solves the change in nanowire morphology caused by removing templates or ligands, showing great application prospects in the fields of catalysis, electronics and optoelectronic equipment.
[0032] The platinum nanowires prepared by the present invention have unique structural characteristics. Such one-dimensional linear structures can be used in fuel cells such as methanol fuel cells and proton exchange membrane batteries, and have good catalytic activity. In addition, the ligand-free synthesized platinum nanowires reduce the cumbersome step of removing the ligands in the catalytic process, and avoid the activity loss caused by the inability to use the active sites blocked by the ligands in the nanostructure, and open up a new way for the synthesis of nanowires.
[0033] This method has a wide deposition potential range of -0.5 V to -7 V. By adjusting the deposition time, the length of platinum nanowires can be controlled on the substrate without templates and small molecule ligands; at the same time, by changing the concentration of the silane coupling agent, the density of the platinum nanowires can be controlled. In addition, the synthesis can also be extended to a conductive substrate, so that the platinum nanowire array can be directly used as a working electrode in the future, providing great application potential in fields such as electrocatalysis. The present invention has a simple process, mild reaction conditions, low cost, and the electro-deposition method for synthesizing nanomaterials has the advantages of precise controllability, simple operation and environmental protection.
[0034] The surface treatment of the substrate in this technology is relatively sensitive, and there are strict requirements on the number of amino groups on the substrate surface. Acid must be added during the amination treatment, such asFigure 1 As shown, the addition of acid promotes the hydrolysis of APTES and inhibits its self-condensation, thereby reducing the number of surface amino groups, so that a uniform and densely distributed platinum nanowire array can be obtained.
[0035] In step (2), platinum nanowires with different densities can be obtained by changing the concentration of the acidified APTES solution.
[0036] In step (5), changing the electrochemical deposition time can obtain platinum nanowire arrays of different lengths.
[0037] At a concentration of 2.4 mM chloroplatinic acid, we determined that the optimal window for the growth of electrodeposited Pt nanowires is between -3 V and -7 V, as Figure 4 As shown in the figure, within this window, the synthesized platinum nanowires show good uniformity and excellent linear morphology. After exceeding the appropriate growth window, that is, when the potential reaches -10 V, the reduction rate in the system is too fast, resulting in platinum not having time to deposit on the substrate and thus being free in the electrolyte, and the electrolyte will turn black, so the density of the nanowires drops significantly, and there are more platinum particles on the substrate; when the potential is too low, the reduction rate is too slow and only spherical particles can be generated.
[0038] In the present invention, we systematically screened the pH value of the electrolyte that affects the synthesis of platinum nanowires. Figure 4 As shown in the figure, when the pH value of the electrolyte drops to 0.85, the hydrogen evolution in the reaction becomes more obvious, competing with the reduction of platinum, and the generation of a large number of bubbles affects the growth of nanowires and tends to form sheets. When the pH value of the electrolyte increases, the sheet structure becomes smaller and smaller, and it tends to grow linearly at this time; until the pH value reaches 1.25, the sheet growth basically disappears. When the pH value is kept within 1.25~2.79, a uniformly distributed and dense platinum nanowire array can be obtained on the substrate. When the pH rises to neutral or alkaline, only spherical nanoparticles can be obtained.
[0039] The present invention also relates to growing platinum nanowire arrays on different substrate materials, such as silicon wafers and some materials with good conductivity, such as carbon paper, carbon cloth, conductive glass, etc. The universality of this substrate allows the conductive material grown with platinum nanowire arrays to be directly used as a working electrode, reducing the inevitable loss of catalysts during the catalyst preparation process and the problem of loose bonding with the electrode, and has great application potential in electrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1The SEM images of whether APTES is used in the substrate pretreatment, the APTES concentration and the different effects of APTES acidification on the growth of nanowires in the present invention, a is the substrate not treated with APTES; be is the substrate treated with different concentrations of APTES, specifically (b) 5 mM; (c) 5×10 -2 mM; (d) 5×10 -3 mM; (e) 5×10 -9 mM; f is the substrate treated with a mixture of 5 mM APTES and acetic acid in an equal volume ratio.
[0041] Figure 2 The SEM images of the substrate treated with different concentrations of APTES acidified solution in the present invention are (a) 5 mM; (b) 5×10 -1 mM; (c) 5×10 -2 mM; (d) 5×10 -3 mM.
[0042] Figure 3 These are SEM images of 2.4 mM chloroplatinic acid in the present invention obtained at different reduction voltages: (a) -1 V; (b) -2 V; (c) -3 V; (d) -7 V; (e) -9 V; and (f) -10 V.
[0043] Figure 4 In the present invention, acid or base is added to 2.4 mM chloroplatinic acid to adjust the pH to (a) 0.85; (b) 1; (c) 1.25; (d) 2.31; (e) 2.79; (f) 3.
[0044] Figure 5 These are SEM images of the cells grown at a reduction potential of -5 V after addition of 1.2 mM chloroplatinic acid for (a) 5 min; (b) 10 min; (c) 30 min; (d) 60 min; (e) 120 min; and (f) 180 min in the present invention.
[0045] Figure 6 These are SEM images of platinum nanowire arrays grown on different substrate surfaces: (a) hydrophobic carbon cloth; (b) hydrophobic carbon paper; (c) conductive glass; (d) hydrophilic carbon paper.
[0046] Figure 7 Using hydrophilic carbon paper as the substrate, the SEM images of Pt nanowires with lengths of 100 nm, 170 nm, 400 nm, and 600 nm were obtained by controlling the deposition time to 10 min, 30 min, 60 min, and 120 min.
[0047] Figure 8Area activity plots obtained by cyclic voltammetry (CV) measurements of Pt nanowires grown on hydrophilic carbon paper and conventional commercial Pt carbon as methanol oxidation catalysts. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with specific implementations and drawings.
[0049] Example 1
[0050] (1) First, the silicon wafer was treated with a plasma cleaner for 10 min to make it hydrophilic. Then, the substrate was treated with triaminopropyltriethoxysilane solution (APTES) for 30 min under acidic conditions. Specifically, the concentrations of triaminopropyltriethoxysilane were 5 mM, 5×10 -2 mM, 5×10 -3 mM, 5×10 -9 mM;
[0051] The acidified solution of APTES refers to a mixture of 5 mM APTES and 17.4 M acetic acid in an equal volume ratio. During the preparation process, APTES is dissolved in ethanol and water in an equal volume ratio of 1:1. During the preparation, ethanol is added first and then water to prevent excessive hydrolysis of the silane coupling agent.
[0052] (2) Take out the substrate from step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution for 2 h;
[0053] (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte;
[0054] (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode. The total volume of the electrolyte is 12 mL, which is mainly composed of water and ethanol, and the volume ratio of water to ethanol is 2:1. Among them, 2.4 mM chloroplatinic acid is used as a metal precursor and dissolved in water. The pH value of the electrolyte is measured to be 2.31.
[0055] (5) The synthesis used a constant potential amperometry method with the potential set at -3 V and a deposition time of 10 min. After deposition, the substrate was washed with ethanol and water and dried before characterization. A black film covered the surface of the substrate, indicating that the platinum nanowire array was successfully synthesized.
[0056] Figure 1The SEM images of whether APTES is used in the substrate pretreatment, the APTES concentration and the different effects of APTES acidification on the growth of nanowires in the present invention, a is the substrate not treated with APTES; be is the substrate treated with different concentrations of APTES, specifically (b) 5 mM; (c) 5×10 -2 mM; (d) 5×10 -3 mM; (e) 5×10 -9 mM; f is the substrate treated with a mixture of 5 mM APTES and acetic acid in an equal volume ratio.
[0057] The products were analyzed by scanning electron microscope. Figure 1 As shown, the substrate without APTES treatment can only obtain a dense layer of platinum nanoparticles, while as the APTES concentration decreases, linear growth gradually occurs on the substrate surface and its density increases; in addition, the substrate treated with the acidified solution of APTES can obtain a uniform and densely grown platinum nanowire array. The nanowires (length of about 500 nm and diameter of 5.5 nm) grown by mixing 5mM APTES and acetic acid in equal volume ratios have the best uniformity in morphology.
[0058] Example 2
[0059] (1) First, the silicon wafer was treated with a plasma cleaner for 10 min to make it hydrophilic. Then, the substrate was treated with triaminopropyltriethoxysilane solution (APTES) for 30 min under acidic conditions. The concentrations of triaminopropyltriethoxysilane were 5 mM and 5×10 -1 mM, 5×10 -2 mM, 5×10 -3 mM, APTES was dissolved in equal volumes of ethanol and water (1:1), ethanol was added first and then water was added during preparation to prevent excessive hydrolysis of the silane coupling agent, and the prepared APTES solution was mixed with equal volumes of 17.4 M acetic acid to treat the substrate;
[0060] (2) Take out the substrate from step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution for 2 h;
[0061] (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte;
[0062] (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode. The total volume of the electrolyte is 12 mL, which is mainly composed of water and ethanol, and the volume ratio of water to ethanol is 2:1. Among them, 2.4 mM chloroplatinic acid is used as a metal precursor and dissolved in water. The pH value of the electrolyte is measured to be 2.31.
[0063] (5) The synthesis used a constant potential amperometry method with the potential set at -3 V and a deposition time of 10 min. After deposition, the substrate was washed with ethanol and water and dried before characterization. A black film covered the surface of the substrate, indicating that the platinum nanowire array was successfully synthesized.
[0064] Figure 2 The SEM images of the substrate treated with different concentrations of APTES acidified solution in the present invention are (a) 5 mM; (b) 5×10 -1 mM; (c) 5×10 -2 mM; (d) 5×10 -3 mM.
[0065] The product was analyzed by scanning electron microscopy. After the substrate was treated with acidified APTES solution, Figure 2 The density of the nanowires shown in the figure gradually decreases with the decrease of APTES concentration, and more nanoparticles are generated. The density of the nanowires grown by mixing 5 mM APTES and acetic acid in equal volume ratio is the best in terms of morphology.
[0066] Example 3
[0067] (1) First, the silicon wafer was treated with hydrophilicity by a plasma cleaner for 10 min, and then the substrate was treated with amino treatment using triaminopropyltriethoxysilane solution (APTES) for 30 min under acidic conditions. Specifically, the concentration of triaminopropyltriethoxysilane was 5 mM (1.10685 mg / mL). APTES was dissolved in ethanol and water in an equal volume ratio (1:1). During the preparation, ethanol was added first and then water to prevent excessive hydrolysis of the silane coupling agent. The prepared APTES was mixed with equal volumes of 17.4 M acetic acid to treat the substrate.
[0068] (2) Take out the substrate from step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution for 2 h;
[0069] (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte;
[0070] (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode. The total volume of the electrolyte is 12 mL, which is mainly composed of water and ethanol, and the volume ratio of water to ethanol is 2:1. Among them, 2.4 mM chloroplatinic acid is used as a metal precursor and dissolved in water. The pH value of the electrolyte is measured to be 2.31.
[0071] (5) The synthesis used a constant potential amperometry method, with the potential set at -1 V to -10 V and a deposition time of 10 min. After deposition, the substrate was washed with ethanol and water and dried before characterization. A black film covered the surface of the substrate, indicating that the platinum nanowire array was successfully synthesized.
[0072] Figure 3 These are SEM images of 2.4 mM chloroplatinic acid in the present invention obtained at different reduction voltages: (a) -1 V; (b) -2 V; (c) -3 V; (d) -7 V; (e) -9 V; and (f) -10 V.
[0073] The products were analyzed by scanning electron microscope. Figure 3 As shown in the figure, under the condition of electrolyte pH value of 2.31, the suitable growth window of platinum nanowires is determined to be -3 V to -7 V. When the reduction voltage is -1 V, only a large number of platinum particles can be obtained on the substrate surface. As the reduction voltage shifts negatively (-2 V), nanowires are gradually generated, and when the reduction voltage reaches -3 V, uniformly distributed and densely grown platinum nanowires can be obtained. Then, when the voltage shifts further negatively to -10 V, the density and length of the nanowires are gradually decreasing. At this time, the platinum is reduced too quickly and most of it enters the electrolyte.
[0074] Example 4
[0075] (1) First, the silicon wafer was treated with hydrophilicity by a plasma cleaner for 10 min, and then the substrate was treated with amino treatment using triaminopropyltriethoxysilane solution (APTES) for 30 min under acidic conditions. Specifically, the concentration of triaminopropyltriethoxysilane was 5 mM (1.10685 mg / mL). APTES was dissolved in equal volumes of ethanol and water in a ratio of 1:1. During the preparation, ethanol was added first and then water to prevent excessive hydrolysis of the silane coupling agent. The prepared APTES was mixed with equal volumes of 17.4 M acetic acid to treat the substrate.
[0076] (2) Take out the substrate from step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution for 2 h;
[0077] (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte;
[0078] (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode. The total volume of the electrolyte is 12 mL, which is mainly composed of water and ethanol, and the volume ratio of water to ethanol is 2:1. Among them, 2.4 mM chloroplatinic acid is used as a metal precursor and dissolved in water. The pH value of the electrolyte is measured to be 2.31, and hydrochloric acid or sodium hydroxide is additionally added to the electrolyte to adjust the pH value.
[0079] (5) The synthesis used a constant potential amperometry method with the potential set at -3 V and a deposition time of 10 min. After deposition, the substrate was washed with ethanol and water and dried before characterization. A black film covered the surface of the substrate, indicating that the platinum nanowire array was successfully synthesized.
[0080] Figure 4 In the present invention, acid or base is added to 2.4 mM chloroplatinic acid to adjust the pH to (a) 0.85; (b) 1; (c) 1.25; (d) 2.31; (e) 2.79; (f) 3.
[0081] The product was analyzed by scanning electron microscope. Figure 4 As shown in the figure, when the pH value of the electrolyte drops to 0.85, the hydrogen evolution in the reaction becomes more obvious, competing with the reduction of platinum, and the generation of a large number of bubbles affects the growth of nanowires and tends to form sheets. When the pH value of the electrolyte increases, the sheet structure becomes smaller and smaller, and it tends to grow linearly at this time; until the pH value reaches 1.25, the sheet growth basically disappears. When the pH value is kept within 1.25~2.79, a uniformly distributed and dense platinum nanowire array can be obtained on the substrate. When the pH rises to neutral or alkaline, only spherical nanoparticles can be obtained.
[0082] Example 5
[0083] (1) First, the silicon wafer was treated with hydrophilicity by a plasma cleaner for 10 min, and then the substrate was treated with amino treatment using triaminopropyltriethoxysilane solution (APTES) for 30 min under acidic conditions. Specifically, the concentration of triaminopropyltriethoxysilane was 5 mM (1.10685 mg / mL). APTES was dissolved in ethanol and water in an equal volume ratio (1:1). During the preparation, ethanol was added first and then water to prevent excessive hydrolysis of the silane coupling agent. The prepared APTES was mixed with an equal volume of 17.4 M acetic acid to treat the substrate.
[0084] (2) Take out the substrate from step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution for 2 h;
[0085] (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte;
[0086] (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode. The total volume of the electrolyte is 12 mL, which is mainly composed of water and ethanol, and the volume ratio of water to ethanol is 2:1. Among them, 1.2 mM chloroplatinic acid is used as a metal precursor and dissolved in water. No additional ligand is added during the synthesis, but a certain amount of 2 M hydrochloric acid is added. The pH value of the electrolyte is measured to be 1.82;
[0087] (5) The synthesis used a constant potential amperometric method with the potential set at -5 V. The deposition time was 5 min, 10 min, 30 min, 60 min, 120 min, and 180 min, respectively. After the deposition, the substrate was washed with ethanol and water and dried before characterization. A layer of black film covered the surface of the substrate, indicating that the platinum nanowire array was successfully synthesized.
[0088] Figure 5 These are SEM images of the cells grown at a reduction potential of -5 V after addition of 1.2 mM chloroplatinic acid for (a) 5 min; (b) 10 min; (c) 30 min; (d) 60 min; (e) 120 min; and (f) 180 min in the present invention.
[0089] The product was analyzed by scanning electron microscopy. The electrolyte condition was that adding acid to 1.2 mM chloroplatinic acid could increase the length of the nanowires to a maximum of nearly 10 μm, while the length of the nanowires grown under the original electrolyte condition (2.4 mM chloroplatinic acid) could only reach about 1 μm. Figure 5 As shown, the length of the visible nanowires increases linearly with the deposition time, with lengths of 250 nm, 500 nm, 1 μm, 1.5 μm, 3 μm, 9.5 μm, and a diameter of 5.5 nm for the platinum nanowires.
[0090] Example 6
[0091] (1) First, a conductive substrate, such as carbon paper, carbon cloth, and conductive glass, is subjected to a hydrophilic treatment for 15 minutes using a plasma cleaning machine. Then, the substrate is subjected to an amination treatment using a triaminopropyltriethoxysilane solution (APTES) for 10 minutes under acidic conditions. Specifically, the concentration of triaminopropyltriethoxysilane is 5 mM (1.10685 mg / mL). APTES is dissolved in ethanol and water in an equal volume ratio (1:1). During the preparation, ethanol is added first and then water to prevent excessive hydrolysis of the silane coupling agent. The prepared APTES is mixed with an equal volume of 17.4 M acetic acid to treat the substrate.
[0092] (2) Take out the substrate from step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution for 2 h;
[0093] (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte;
[0094] (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode. The total volume of the electrolyte is 12 mL, which is mainly composed of water and ethanol, and the volume ratio of water to ethanol is 2:1. Among them, 1.2 mM chloroplatinic acid is used as a metal precursor and dissolved in water. In addition, 2 M hydrochloric acid is added to the electrolyte, and the pH value of the electrolyte is measured to be 1.82.
[0095] (5) The synthesis was performed using a constant potential amperometry method with the potential set at −0.5 V and a deposition time of 10 min. After deposition, the samples were washed with ethanol and water and dried before characterization.
[0096] Figure 6 These are SEM images of platinum nanowire arrays grown on different substrate surfaces: (a) hydrophobic carbon cloth; (b) hydrophobic carbon paper; (c) conductive glass; (d) hydrophilic carbon paper.
[0097] The products were analyzed by scanning electron microscope. Figure 6 As shown in the figure, based on the above-mentioned control experiment with the substrate being a silicon wafer, the optimal synthesis conditions of platinum nanowires are obtained and directly applied to the conductive substrate. Since the internal resistance of the silicon wafer is much larger than that of the conductive substrate, the growth potential of the platinum nanowires on the conductive substrate is adjusted to -0.5 V as the best. Among them, the nanowires grown on the hydrophobic carbon cloth / carbon paper are a mixture of nanowires and nanoparticles, the density of nanowires grown on the conductive glass is very low, and the nanowires grown on the hydrophilic carbon paper are the best in terms of uniformity and morphology. And as Figure 7 As shown in the figure, by adjusting the deposition time, we can obtain platinum nanowires of different lengths on hydrophilic carbon paper. Deposition for 10 min, 30 min, 60 min, and 120 min can obtain nanowires with lengths of 100 nm, 170 min, 400 nm, and 600 nm. In addition, the platinum nanowires obtained on the conductive substrate can be directly used for catalytic reactions, reducing problems such as catalyst loss or weak binding force between the catalyst and the electrode in the traditional catalyst preparation process, which greatly promotes the development of electrocatalysis.
[0098] Then, electrochemical tests were performed using three-electrode tests. The counter electrode was a graphite rod; the reference electrode was a saturated calomel electrode (SCE); and the working electrode was a hydrophilic carbon paper on which platinum nanowires were grown. The electrolyte was a 1 M KOH and 0.5 M methanol aqueous solution. The scan rate of the cyclic voltammetry (CV) test was 50 mV / s.
[0099] Figure 8 Area activity plots obtained by cyclic voltammetry (CV) measurements of Pt nanowires of different lengths grown on hydrophilic carbon paper and conventional commercial Pt carbon as methanol oxidation catalysts.
[0100] like Figure 8 As shown in the figure, the electrochemical test results show that the longer the length of the platinum nanowire, the greater its area activity. The area activity of the platinum nanowire with a length of 600 nm can reach 217 mA / cm -2 , while the area activity of commercial Pt / C is only 17.4 mA / cm -2 Therefore, the current density of the ligand-free grown platinum nanowires shows a 10-fold higher methanol oxidation catalytic efficiency than that of traditional commercial platinum carbon, and its forward oxidation peak potential has a delayed phenomenon, indicating that it has enhanced inhibition on carbon-containing oxides.
[0101] The present invention is not limited to the specific technical solutions described in the above embodiments. Any modification or equivalent replacement of the present invention to achieve the same technical effect is within the protection scope of the present invention.
Claims
1. A ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate, characterized in that : Includes the following steps: (1) First, the substrate is treated to be hydrophilic by a plasma cleaner, and then the substrate is treated to be amino by using triaminopropyltriethoxysilane solution APTES under acidic conditions; (2) taking out the substrate in step (1), rinsing off excess APTES solution, and immersing the substrate in a platinum particle solution; (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte; (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode; the electrolyte is composed of water and ethanol, in which chloroplatinic acid is used as the metal precursor, and no additional ligand is added; (5) The electro-deposition synthesis method uses a constant potential amperometric method, with the potential set at -0.5 V to -7 V and the deposition time controlled at 5 min to 180 min to synthesize platinum nanowire arrays.
2. The ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate according to claim 1, characterized in that : Includes the following steps: (1) First, the substrate is treated to be hydrophilic by a plasma cleaner, and then the substrate is treated to be amino by using a triaminopropyltriethoxysilane solution (APTES) under acidic conditions; (2) Take out the substrate in step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution; (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte; (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode; the electrolyte is composed of water and ethanol, in which chloroplatinic acid is used as the metal precursor, and no additional ligand is added; The pH value of the electrolyte is 1.25~2.79; (5) The electrodeposition synthesis method uses the constant potential amperometry method, with the potential set at -0.5 V to -7 V and the deposition time controlled at 5 min-180 min. After the electrodeposition reaction is completed, the silicon wafer is removed, rinsed with water and ethanol, and dried before characterization.
3. The ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate according to claim 1, characterized in that: In step (1), the concentration of triaminopropyltriethoxysilane is 5 mM.
4. The ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate according to claim 1, characterized in that: The substrate is a silicon wafer, hydrophobic carbon paper, hydrophilic carbon paper, hydrophobic carbon cloth or conductive glass.
5. A ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate according to claim 1, characterized in that : In step (1), the acid used to treat the substrate is acetic acid.
6. A ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate according to claim 1, characterized in that : In step (4), the total volume of the electrolyte is 12 mL, the volume ratio of water to ethanol is 2:1, the concentration of chloroplatinic acid is 1.2-2.4 mM as a metal precursor, dissolved in water, and no additional ligand is added during the synthesis.
7. A ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate according to claim 1, characterized in that :The substrate is hydrophilic carbon paper.
8. The ligand-free electrodeposition method for synthesizing platinum nanowire arrays on a substrate according to claim 1, characterized in that : Includes the following steps: (1) First, the substrate was treated with hydrophilicity by a plasma cleaner for 10 min, and then the substrate was treated with amino treatment using triaminopropyltriethoxysilane solution APTES for 30 min under acidic conditions. The concentration of triaminopropyltriethoxysilane was 5 mM. APTES was dissolved in equal volumes of ethanol and water in a ratio of 1:
1. During the preparation, ethanol was added first and then water to prevent excessive hydrolysis of the silane coupling agent. After the APTES was prepared, it was mixed with an equal volume of 17.4 M acetic acid to treat the substrate. (2) Take out the substrate in step (1), rinse off the excess APTES solution, and immerse it in a 3-5 nm platinum particle solution for 2 h; (3) taking out the substrate in step (2), washing away the excess platinum particle solution, and then preparing an electrolyte; (4) The electrodeposition adopts a three-electrode system, in which saturated Ag / AgCl is used as the reference electrode, the carbon rod is used as the counter electrode, and the substrate is used as the working electrode. The total volume of the electrolyte is 12 mL, which is mainly composed of water and ethanol, and the volume ratio of water to ethanol is 2:
1. Among them, 1.2 mM chloroplatinic acid is used as a metal precursor and dissolved in water. No additional ligand is added during the synthesis, but a certain amount of 2 M hydrochloric acid is added. The pH value of the electrolyte is measured to be 1.82; (5) The constant potential amperometry method was used in the synthesis, and the deposition time was 120 min. After the deposition, it was washed with ethanol and water and dried before characterization. The surface of the substrate was covered with a layer of black film, indicating that the platinum nanowire array was successfully synthesized.
9. Use of the platinum nanowire array prepared by the method according to any one of claims 1 to 8, characterized in that :Platinum nanowire arrays can be used in fuel cells or electrochemical catalysis.
Citation Information
Patent Citations
Method and system for preparation of highly porous and preferentially-oriented {100} platinum nanowires and thin films
CA2772458A1
Superfine three-dimensional platinum nanowire array growing on substrate under control of strong ligand, and method thereof
CN111370716A
Preparation method and application of coralline Pt nanowire catalytic electrode
CN114481193A
Template-free electrochemical synthesis method of gold nanowire
CN117051436A
Cited By
Universal preparation method and device for metal micro-nano structure
CN121571660A
A general method and device for preparing metal micro-nano structures
CN121571660B